2022
DOI: 10.3390/cells11142130
|View full text |Cite
|
Sign up to set email alerts
|

Role of Circular RNA in Brain Tumor Development

Abstract: Central nervous system tumors are a leading cause of cancer-related death in children and adults, with medulloblastoma (MB) and glioblastoma (GBM) being the most prevalent malignant brain tumors, respectively. Despite tremendous breakthroughs in neurosurgery, radiation, and chemotherapeutic techniques, cell heterogeneity and various genetic mutations impacting cell cycle control, cell proliferation, apoptosis, and cell invasion result in unwanted resistance to treatment approaches, with a 5-year survival rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 117 publications
(155 reference statements)
0
10
0
Order By: Relevance
“…Current knowledge of circRNA has characterized it as noncoding RNA, and an increasing number of circRNAs have been found to be associated with pretranscription/post-transcription processes by acting as miRNA sponges, protein decoys, splicing regulators, and transcription and chromatin modifiers [ 35 , 36 , 37 ]. Because of the characteristics of circRNA, including its stable structure due to its covalently closed loops [ 38 ], redundant expression level, and easy detection, it is currently considered an optimal diagnostics biomarker for various diseases [ 39 , 40 , 41 ]. In MMD, very few diagnostic biomarkers have been identified and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge of circRNA has characterized it as noncoding RNA, and an increasing number of circRNAs have been found to be associated with pretranscription/post-transcription processes by acting as miRNA sponges, protein decoys, splicing regulators, and transcription and chromatin modifiers [ 35 , 36 , 37 ]. Because of the characteristics of circRNA, including its stable structure due to its covalently closed loops [ 38 ], redundant expression level, and easy detection, it is currently considered an optimal diagnostics biomarker for various diseases [ 39 , 40 , 41 ]. In MMD, very few diagnostic biomarkers have been identified and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the level of individual miRNAs, the miRNAs with the highest prognostic value for GBM were selected [ 72 ], indicating that that the diagnosis of GBM is also possible on the basis of the analysis of miRNA from the blood and cerebrospinal fluid of patients [ 73 , 74 , 75 ]. Functional analysis of individual GBM-specific miRNAs indicates that they can act as both oncogenes and tumor suppressors, are responsible for developing resistance to chemotherapy and radiotherapy, stimulate neo-angiogenesis and cell proliferation, and regulate the cell cycle and apoptosis [ 76 , 77 , 78 , 79 , 80 ] ( Table 2 ).…”
Section: Mirnas Expression In Gbmmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are significant in cancer diagnosis and potential therapeutic targets. They are covalently bonded single-stranded closed circRNA molecules without poly(A) tail at the 3′ end or a 5′ end-cap . In an experiment, it was found that Circ-FBXW7 and FBXW7–185aa have possible prognostic relevance in brain cancer .…”
Section: Exosomal Noncoding Rna Transport and Its Impact On Glioblast...mentioning
confidence: 99%
“…They are covalently bonded single-stranded closed circRNA molecules without poly(A) tail at the 3′ end or a 5′ end-cap. 39 In an experiment, it was found that Circ-FBXW7 and FBXW7− 185aa have possible prognostic relevance in brain cancer. 40 The current research investigation mentions that circRNAs has association with pathogenesis of GBM.…”
Section: Exosomal Noncoding Rna Transport and Its Impact On Glioblast...mentioning
confidence: 99%